A vitronectin‐derived peptide prevents and restores alveolar bone loss by modulating bone re‐modelling and expression of RANKL and IL‐17A. (16th June 2022) - Lee, Junbeom; Min, Hong Ki; Park, Cho Yeon; Kang, Hyun Ki; Jung, Sung Youn; Min, Byung‐Moo
Abstract: Aim: This study investigated whether a vitronectin‐derived peptide (VnP‐16) prevents and/or reverses alveolar bone resorption induced by ligature‐induced periodontitis in rodents and identified the underlying mechanism. Materials and Methods: We evaluated the effects of VnP‐16 on osteogenic differentiation in human periodontal ligament cells (hPDLCs), lipopolysaccharide‐induced inflammatory responses in gingival fibroblasts, and immune response in T lymphocytes. Ligature‐induced periodontitis was induced by ligating the bilateral mandibular first molars for 14 days in rats and for 7 days in mice ( n  = 10/group). VnP‐16 (100 μg/10 μl) was applied topically into the gingival sulcus of rats via intra‐sulcular injection, whereas the peptide (50 μg/5 μl) was administered directly into the gingiva of mice via intra‐gingival injection. To evaluate the preventive and therapeutic effects of VnP‐16, micro‐computed tomography analysis and histological staining were then performed. Results: VnP‐16 promoted osteogenic differentiation of periodontal ligament cells and inhibited the production of lipopolysaccharide‐induced inflammatory mediators in gingival fibroblasts. Concomitantly, VnP‐16 modulated the host immune response by reducing the number of receptor activator of NF‐κB ligand (RANKL)‐expressing lipopolysaccharide‐stimulated CD4 + and CD8 + T cells, and by suppressing RANKL and interleukin (IL)‐17A production. Furthermore, local administration of VnP‐16 in rats and mice significantly prevented and reversed alveolar bone loss induced by ligature‐induced periodontitis. VnP‐16 enhanced osteoblastogenesis and simultaneously inhibited osteoclastogenesis and suppressed RANKL and IL‐17A expression in vivo. Conclusions: Our findings suggest that VnP‐16 acts as a potent therapeutic agent for preventing and treating periodontitis by regulating bone re‐modelling and immune and inflammatory responses.